Pelatihan Pemantapan MS. Office Bagi Kader Desa - Havid Syafwan; Riki Andri Yusda; Pristiyanilicia Putri (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
This Community Service activity is carried out in the form of training for village cadres in using Microsoft Office software in utilizing information technology at this time. This training material was delivered to the community members in Dadimulyo Village, Kisaran Barat District, Kab. Asahan, which amounted to approximately 30 people. This service activity was carried out using lectures, demonstrations, and exercises accompanied by questions and answers. The lecture method is used to explain the introductory concept of the introduction of Microsoft Office software as one of the media in facilitating human work. The demonstration method is used to show a work process, namely the stages of introducing the tools that exist in Microsoft Office software and knowing each of their functions, while the training method is to practice directly using the application. While the question and answer method are to allows participants to consult to overcome obstacles in understanding the material that has been obtained. The final result of this activity is expected to provide knowledge to Dadimulyo village cadres regarding the use of Ms. Office, especially Ms. Word in the process of making reports to the village head.